The role and impact of female extension officers on the participation of women in export crop production in Papua New Guinea - Hamago, Matilda Rondy (Curtin University, 2019)
The study investigated the roles and impact of female extension officers on the participation of smallholder women farmers in the production of Papua New Guinea’s major export commodity crops of cocoa, coffee and oil palm. The study found that female extension officers in the different commodity crops experienced different forms of gender bias, but when such biases were addressed women farmers were empowered to participate more fully in agricultural development.